Capital Flows and Their Macroeconomic Effects in India - Kohli, Renu (IMF Working Papers; Working Paper ;, 2001)
This paper documents trends in movement and composition of capital flows into India in a comparative perspective, examines the impact of these flows upon key macroeconomic variables in the economy, and dwells on implications for economic policy. We find that an inflow of foreign capital results in a real appreciation and has a significant impact on domestic money supply. During a capital surge, these effects have been countered through intervention and sterilization. The paper concludes with a discussion on the costs of these policies in the event of a heavy inflow of foreign capital into India.